2023
DOI: 10.1039/d3cp03261b
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the thermometric behaviors of Er3+/Yb3+/Ho3+-tridoped La2Mo3O12 polychromatic upconverting microparticles via adjusting spatial mode and a sensing strategy

Abstract: To meet the needs of contactless optical thermometry, Er3+/Yb3+/Ho3+-tridoped La2Mo3O12 (LMO) microparticles were designed. Excited at 980 nm light, the resultant compounds emit glaring upconversion (UC) emissions and their emitting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…from 303 to 623 K), the prepared samples still exhibit the pure orthorhombic phase, implying their high thermal stability, which enables their promising applications in a high-temperature environment. Moreover, according to the obtained XRD patterns, it is evident that the cell volume shows a significant downward tendency at elevated temperatures, namely, it decreases from about 1128.757 to 1121.443 Å 3 , as presented in 32 Moreover, two peaks at 1624 and 3453 cm −1 , which are assigned to O-H vibrations, 33 are also observed in the studied samples. On the other hand, the light harvesting capacities of the final products were characterized by UV-vis diffuse-reflectance spectroscopy and the corresponding spectra are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…from 303 to 623 K), the prepared samples still exhibit the pure orthorhombic phase, implying their high thermal stability, which enables their promising applications in a high-temperature environment. Moreover, according to the obtained XRD patterns, it is evident that the cell volume shows a significant downward tendency at elevated temperatures, namely, it decreases from about 1128.757 to 1121.443 Å 3 , as presented in 32 Moreover, two peaks at 1624 and 3453 cm −1 , which are assigned to O-H vibrations, 33 are also observed in the studied samples. On the other hand, the light harvesting capacities of the final products were characterized by UV-vis diffuse-reflectance spectroscopy and the corresponding spectra are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 55%
“…As revealed, all the samples exhibit an intense absorption band in the range of around 500–1450 cm −1 , corresponding to the overlapped vibrations of [WO 4 ] 2− , [PO 4 ] 3− and [ZrO 4 ] 4− groups. 32 Moreover, two peaks at 1624 and 3453 cm −1 , which are assigned to O–H vibrations, 33 are also observed in the studied samples. On the other hand, the light harvesting capacities of the final products were characterized by UV-vis diffuse-reflectance spectroscopy and the corresponding spectra are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Based on the collected findings, it can be concluded that the designed thermometer is suitable for thermal sensing in both biological and industrial systems. The findings demonstrate that the NSYM-based phosphor exhibits superior temperature resolution compared to the Gd 2 Mo 3 O 12 :Yb 3+ /Er 3+ and La 2 Mo 3 O 12 :Yb 3+ /Er 3+ /Ho 3+ phosphors and Yb 3+ /Tm 3+ -Y 2 Mo 3 O 12 ceramics within the specified operating temperature range. ,, The results of our study indicate that NSYM-upconverting materials, which exhibit a high degree of sensitivity to thermal changes and little error in temperature measurements, have great potential for optical thermometry using the LIR technique.…”
Section: Resultsmentioning
confidence: 59%